Translation of New Rules on International Jurisdiction of Japanese Courts in Family Matters - Okuda, Yasuhiro (Zeitschrift für Japanisches Recht, 2021)
I. Act on Litigation in Personal Matters II. Act on Procedure in Family Matters III. Code of Civil Execution